2020
DOI: 10.1101/2020.02.27.967950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High school Internship Program in Integrated Mathematical Oncology (HIP IMO) – five-year experience at Moffitt Cancer Center

Abstract: Modern cancer research, and the wealth of data across multiple spatial and temporal scales, has created the need for researchers that are well-versed in the life sciences (cancer biology, developmental biology, immunology), medical sciences (oncology) and natural sciences (mathematics, physics, engineering, computer sciences). College undergraduate education is traditionally provided in disciplinary silos, which creates a steep learning curve at the graduate and postdoctoral levels that increasingly bridge mul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…17 To better prepare students for future careers at the interdisciplinary interface, Enderling et al identified a need to educate junior and senior high school students about integrating mathematical and biological skills, through the lens of mathematical oncology, known as the High school Internship Program in Integrated Mathematical Oncology (HIP IMO) at Moffitt Cancer Center. 18 Modern cancer research, and the wealth of data across multiple spatial and temporal scales, has created the need for researchers that are well versed in the life sciences (cancer biology, developmental biology, immunology), medical sciences (oncology), and natural sciences (mathematics, physics, engineering, computer sciences). 18 College undergraduate education traditionally occurs in disciplinary silos, which creates a steep learning curve at the graduate and postdoctoral levels that increasingly bridge multiple disciplines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 To better prepare students for future careers at the interdisciplinary interface, Enderling et al identified a need to educate junior and senior high school students about integrating mathematical and biological skills, through the lens of mathematical oncology, known as the High school Internship Program in Integrated Mathematical Oncology (HIP IMO) at Moffitt Cancer Center. 18 Modern cancer research, and the wealth of data across multiple spatial and temporal scales, has created the need for researchers that are well versed in the life sciences (cancer biology, developmental biology, immunology), medical sciences (oncology), and natural sciences (mathematics, physics, engineering, computer sciences). 18 College undergraduate education traditionally occurs in disciplinary silos, which creates a steep learning curve at the graduate and postdoctoral levels that increasingly bridge multiple disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…18 Modern cancer research, and the wealth of data across multiple spatial and temporal scales, has created the need for researchers that are well versed in the life sciences (cancer biology, developmental biology, immunology), medical sciences (oncology), and natural sciences (mathematics, physics, engineering, computer sciences). 18 College undergraduate education traditionally occurs in disciplinary silos, which creates a steep learning curve at the graduate and postdoctoral levels that increasingly bridge multiple disciplines. Numerous colleges have begun to embrace interdisciplinary curricula, but students who double major in mathematics (or other quantitative sciences) and biology (or medicine) remain scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors share specific project examples and QR tools used successfully in their classrooms and offer views on pedagogy for how to best prepare a "more confident and able teacher workforce for the next generation of K-12 students." Enderling et al (2020) have run a "High school Internship Program in Integrated Mathematical Oncology (HIP IMO)" for the past 5 years at Moffitt Cancer Center in Florida. The authors are leaders in the evolutionary therapy approach to cancer through which teachers learn about contemporary research devoted to extending peoples' lives in a dignified, respectful way that avoids the metaphorically militaristic approach.…”
Section: Connectionsmentioning
confidence: 99%